Jeffrey Paul Lyon, Syriac Gospel Translations: A Comparison of the Language and Diatessaron Method used in the Old Syriac, the Diatessaron and the Peshitto, CSCO 548, Subsidia 88, Louvain 1994, ss. 235 - Woźniak, Jerzy (Vox Patrum, 2000)
review